Enhancement of ethanol production from synthetic medium model of hydrolysate of macroalgae. (August 2018) - Sayed, Walaa; Cabrol, Audrey; Abdallah, Rawa; Taha, Samir; Amrane, Abdeltif; Djelal, Hayet
Abstract: Among biomass materials available, macroalgae is a promising alternative to traditional energy crops. The absence of lignin, a high growth rate and a richness of fermentable sugars and nitrogen, are real gains for a competitive ethanol production. But the presence of salts can be an obstacle to obtain relevant performances. Experiments were carried out with a synthetic medium adjusted on algal hydrolysate composition in order to reduce resource limitations and variations of composition. The behavior of four yeast strains for ethanol production was investigated: Candida guilliermondii, Scheffersomyces stipitis, Kluyveromyces marxianus and Saccharomyces cerevisiae . Glucose, which is the most abundant sugar in the targeted algal hydrolysate ( Ulva spp), was completely assimilated by all of the considered strains, even in the presence of salts at levels found in macroalgal hydrolysates (0.25 M of sodium chloride and 0.21 M of sulfate). The use of peptone as nitrogen source enhanced kinetics of consumption and production. For instance, the rate of ethanol production by S. cerevisiae in the presence of peptone was six times higher than that obtained using ammonium, 0.6 and 0.1 g L −1  h −1 respectively. In the presence of salts, the rates of glucose consumption and ethanol production were lowered for the considered strains, except for K. marxianus . Nevertheless, S. cerevisiae could be the most promising strain to valorize Ulva spp hydrolysate in bioethanol, in terms of ethanol produced (7.5–7.9 g L −1 ) whether in the presence or in absence of salts.